First insights on the bacterial fingerprints of live seahorse skin mucus and its relevance for traceability - Cohen, Felipe P.A. [UNESP]; Pimentel, Tânia; Valenti, Wagner C. [UNESP]; Calado, Ricardo (Elsevier, 2018)
Developing a technique to trace the geographic origin of live seahorses is paramount to increase trade regulation and foster conservation. The present study evaluated for the first time the suitability of using bacterial fingerprints present in live seahorse skin mucus to trace their origin. Bacterial 16S rDNA fragments were retrieved from seahorse mucus in a non-invasive and non-destructive way, with their profile (fingerprint) being determined using denaturing gradient gel electrophoresis (DGGE). Bacterial fingerprints were compared among seahorses: (1) originating from different geographic origins sampled at the same period; (2) originating from the same location but sampled one month apart; and (3) originating from specimens in the wild and after being stocked in captivity for 40 and 80 days. Similarities in bacterial fingerprints were determined using hierarchical cluster analysis. Results showed that geographic location affected the bacterial fingerprints of wild seahorses and that specimens sampled in the same location displayed a higher level of similarity. This finding supports that this methodological approach holds the potential to reveal local signatures and trace the origin of live seahorses. Bacterial communities from wild seahorses varied over short-time periods, with this natural variability being a potential constraint that may limit the comparison of specimens collected over long periods. Bacterial fingerprints displayed by wild specimens significantly shifted after 40 days in captivity, with a higher level of similarity being recorded for seahorses after 40 or 80 days in captivity, than when compared with those displayed in the wild. This stabilization of the bacterial community under captive conditions shows the potential that bacterial fingerprints may hold for aquaculture, as these can be used as unique signature to trace seahorses to their production facility.
Keywords: Bacterial communities; Hippocampus; Marine ornamentals; Microbiological barcodes